TINJAUAN PUSTAKA PENGEMBANGAN E-MODUL PUISI 'PULANG' KARYA ISBEDY STIAWAN Z.S INTEGRASI SASTRA ANALISIS SOSIAL - Nur, Kiki Zakiah; Sumarti; Samhati, Siti; Widodo, Mulyanto; Ariyani, Farida (UNDIKMA, 2026)
This study aims to systematically review the development of poetry literature e-modules that integrate social analysis in literary learning, with a specific focus on the poem Pulang by Isbedy Stiawan Z.S. The research is motivated by the dominance of poetry e-modules that emphasize structural and aesthetic elements while neglecting the social realities and ideological contexts represented in literary texts. Using a descriptive qualitative approach with a Systematic Literature Review (SLR) method, this study analyzed scholarly articles, theses, dissertations, and academic books related to e-module development, poetry learning, and social analysis in literature. Data were collected from national and international academic databases using predefined keywords and selection criteria. The findings reveal that most existing poetry e-modules focus on form-based appreciation, technological innovation, and local wisdom, but rarely integrate explicit social analysis addressing issues such as marginalization, poverty, and social inequality. This gap indicates the need for e-modules that position poetry as a medium for critical reflection and social awareness. Based on the review, this study proposes a conceptual direction for developing a poetry e-module on Pulang that integrates sociological and critical literacy approaches to enhance students’ social literacy, critical thinking, and cultural awareness. The study concludes that poetry e-modules grounded in social analysis are essential to support meaningful, contextual, and transformative literature learning aligned with 21st-century educational demands.